2018
DOI: 10.1371/journal.pone.0206209
|View full text |Cite
|
Sign up to set email alerts
|

Prion-like protein gene (PRND) polymorphisms associated with scrapie susceptibility in Korean native black goats

Abstract: The polymorphisms of the prion protein (PRNP) gene, which encodes normal prion proteins (PrP), are known to be involved in the susceptibility of prion diseases. The prion-like protein (Doppel) gene (PRND) is the paralog of the PRNP gene and is closely located downstream of the PRNP gene. In addition, the polymorphisms of PRND correlate with disease susceptibility in several animals. We analyzed the genotype and allele frequencies of PRND polymorphisms in 246 Korean native black goats and found a total of six s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…The prion gene family consists of four members, the PRNP gene, prion-like protein gene ( PRND ), prion-related protein gene ( PRNT ) and SPRN gene 3036 . The former three genes are located on chromosome 13 and a strong genetic LD among these genes has been shown in previous studies 3638 . In addition, the scrapie susceptibility-related PRNP SNPs showed a strong LD with PRND and PRNT SNPs.…”
Section: Discussionsupporting
confidence: 52%
“…The prion gene family consists of four members, the PRNP gene, prion-like protein gene ( PRND ), prion-related protein gene ( PRNT ) and SPRN gene 3036 . The former three genes are located on chromosome 13 and a strong genetic LD among these genes has been shown in previous studies 3638 . In addition, the scrapie susceptibility-related PRNP SNPs showed a strong LD with PRND and PRNT SNPs.…”
Section: Discussionsupporting
confidence: 52%
“…To identify the disease-related polymorphisms in various species, we tried to study the prion protein gene family, including PRNP, PRND and prion-related protein (PRNT) genes (Jeong et al, 2005d;Jeong et al, 2013;Kim and Jeong, 2017a,b;Jeong et al, 2018;Kim and Jeong, 2018a,b,c;Kim et al, 2018;Won et al, 2019). In previous studies, we found only two insertion and deletion polymorphisms in the chicken PRNP gene and one SNP in the horse PRNP gene (Kim and Jeong, 2018b;Kim et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Structural similarities with the PRNP gene and an association with prion disease have been reported in previous studies [44]. Recently, a strong genetic linkage between the PRNP gene and PRND gene was identified, and scrapie-associated SNPs were strictly linked to the genotype of the PRND gene [38,41]. Because those studies have been performed in prion disease-susceptible species, it is elusive whether strong genetic linkage was a prion disease-susceptible factor or a general property among prion gene families.…”
Section: Discussionmentioning
confidence: 82%
“…According to case-controlled studies comparing the genetic distribution of PRND gene polymorphisms in codons 26, 56, 132 and 174 and 3’ untranslated region (UTR) +28, these polymorphisms were involved in the susceptibility to scrapie, BSE and sporadic CJD in ruminants and humans [36,37,38,39,40]. In addition, recent studies have reported a strong linkage disequilibrium (LD) between the PRNP gene and PRND gene in prion disease-susceptible species, sheep and goats [38,41]. However, no study has been conducted on the genetic characteristics of PRND in dogs.…”
Section: Introductionmentioning
confidence: 99%